Vitality of work involvement in mediation: The effect of organizational justice on organizational citizenship behavior - D. Sujono; Billy Tunas; I Ketut R Sudiarditha (Management Science Letters, 2019)
This paper performs an investigation on Organizational Citizenship Behavior (OCB) head of the biMBA-AIUEO unit in DKI Jakarta Province, which is a franchise brand of kindergarten schools in Jakarta. The purpose of the research, is to know and analyze: the direct influence of Organizational Justice on OCB unit head biMBA-AIUEO; the direct influence of Work Involvement on OCB; the direct influence of Organizational Justice on the Work Involvement, and the indirect effect of Organizational Justice on OCB head of the biM-BA-AIUEO unit, with Work Involvement as mediation. The study used 140 samples of head of the biMBA-AIUEO unit in DKI Jakarta Province, and collected data by distributing questionnaires. The research uses quantitative methods and data processing using the path analysis. The results of this study prove that Organi-zational Justice had a positive and significant direct effect on OCB. Organizational Justice that are treated well can be perceived positively for employees to increase their OCB. Research results from work involvement have positive and significant effects on OCB. Even, Work Involvement has the most influence on OCB. This confirms that, high work involvement will also increase their OCB. Likewise, the results of the organization justice have a positive effect on work involvement. This reflects, that employees who are treated fairly by the organization will feel happy and can be a stimulus for them to be more actively involved in work. Whereas Organizational Justice has a positive and significant indirect effect on OCB through the mediation of Work Involvement. Employees who are treated fairly will feel happy, so they can stimulate themselves actively involved in work. This condition then, inspires and stimulates subordinates willing to do extra work that reflects OCB.